2020
DOI: 10.22271/chemi.2020.v8.i2j.8836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano NPK and straight fertilizers on yield, economics and agronomic indices in baby corn (Zea mays L.)

Abstract: A field experiment was conducted in sandy clay loam soil at Campus Farm, M.S. Swaminathan School of Agriculture, R. Sitapur, CUTM, Paralakhemundi to study the fertilizer use efficiency of nano NPK and straight fertilizers with and without organic sources on baby corn (Zea mays L.) during winter of 2018-19. The experiment was laid out in randomized complete block design with three replications and 12 treatments. The treatments comprise of nano NPK, straight fertilizers and organics (vermicompost and azotobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…The application of Nano NPK through spraying showed superior results as it had a longerlasting effect and influenced the physiological processes within the plant cells. These findings are consistent with the results reported by Sankar et al (2020), Yomso and Menon (2021), and Massey and Gaur (2014).…”
Section: Plant Heightsupporting
confidence: 93%
“…The application of Nano NPK through spraying showed superior results as it had a longerlasting effect and influenced the physiological processes within the plant cells. These findings are consistent with the results reported by Sankar et al (2020), Yomso and Menon (2021), and Massey and Gaur (2014).…”
Section: Plant Heightsupporting
confidence: 93%
“…Greater AGR was mainly due to increased leaf number, leaf area and leaf area duration of plant leading to higher photosynthesis by higher nutrient availability. These results validate the findings of Sankar et al (2020) who also indicated the positive effects of nitrogen on AGR of wheat crop.…”
Section: Growth Indicessupporting
confidence: 90%
“…The use of nano NPK fertilizers in potatoes at 50% of the recommended level showed higher values of NPK nutrient use efficiency (Azeim et al, 2020). maximum Agronomic efficiency, apparent nutrient recovery and partial factor productivity were recorded with the application of nano NPK fertilizer alone when compared to other treatments in maize (Sankar, 2020).…”
Section: Nano Fertilizers On Nutrient Use Efficiencymentioning
confidence: 90%